The grammar of politics and performance - Rai, Shirin; Reinelt, Janelle G. (Interventions, 2015)
"This volume brings together important work at the interstection of politics and performance studies. While the languages of theatre and performance have long been deployed by other disciplines such as psychology (Freud's primal 'scene'), sociology (Goffman's 'backstage'), and politics (politicians 'play' to the public, stage debates), this metaphorical attribution has seldom been taken seriously and pursued systematically to discover the actual nature of the relationship between performance as a set of behavioural practices and the forms and the transactions of these other realms"--